Slurry erosion behaviour and mechanism of HVOF sprayed micro-nano structured WC-CoCr coatings in NaCl medium. (August 2020) - Huang, Yan; Ding, Xiang; Yuan, Cheng-Qing; Yu, Zhong-Kun; Ding, Zhang-Xiong
Abstract: In this work, we fabricate nanostructured, bimodal, and multimodal WC-10Co4Cr coatings via two high velocity oxy-fuel (HVOF) systems and investigate the coatings' microstructure, mechanical, electrochemical properties and slurry erosion resistance in 3.5 wt% NaCl solution. The multimodal coating, with a dense microstructure, exhibits lowest decarburization and highest resistance to both corrosion and slurry erosion. The slurry erosion resistance of multimodal coating is enhanced approximately 18% and 11% than the nanostructured and bimodal coatings. However, the performance can easily drop to the worst by changing the HVOF spraying method. The outstanding performance can be attributed to uniform distribution of the multiscale WC grains in the multimodal coating, which effectively reduces the material loss rate during corrosion-accelerated erosion in NaCl solution. Highlights: Various structured WC-10Co4Cr coatings are deposited by two HVOF processes. The multiscale WC particles are evenly distributed in multimodal coating. The multimodal WC-10Co4Cr coating exhibits the best comprehensive performance. Crack growth is the dominate mechanism of coatings' slurry erosion behavior. High corrosion resistance is critical to reduce erosion rate in NaCl solution.